The Inquiry Into The Influence Of The Underwater Scattering Layer On Seabeam And The Tentative Idea Of The Application Of The Acoustic Properties Of Manganese Nodules - Cheng Xiangzhou (International Marine Minerals Society, 1996)
The China Ocean Mineral Resources Research and Development Association (COMRA) conducted a topographic survey in its deep seabed claim area with the SeaBeam system in 19475. After analyzing the data, it was determined that there is a group of living things several hundreds of meters in depth that significantly affect the sound waves in the frequency range of interest. We will attempt to investigate more about such influences. Physical model testing is an important means for studying the theory, and for development of the technology for geophysical prospecting. Because the manganese nodules are distributed over the sea floor in irregular patterns, it is hoped that study of the acoustic properties of manganese nodules by means of physical model testing can improve interpretation of the data of the multi-beam system and the SeaBeam system. This will provide a more reliable basis for delimiting the mineral site and evaluating the reserves in the Pioneer area of China.